2013
DOI: 10.1186/1471-2407-13-177
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chemotherapy-associated neutrophil/ lymphocyte counts on prognosis of adjuvant chemotherapy in colorectal cancer

Abstract: BackgroundLeukocytes play an important role in cancer development. However, the impact of chemotherapy-associated neutropenia/lymphopenia on the prognosis of adjuvant chemotherapy is unknown. Here, we aimed to explore the impact of chemotherapy-associated neutrophil/lymphocyte counts on prognosis of adjuvant chemotherapy in colorectal cancer (CRC) and the risk factors for developing neutropenia/lymphopenia which showed impact on the prognosis of CRC receiving adjuvant chemotherapy.MethodsFrom February 2003 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
4
24
1
Order By: Relevance
“…Chu-Yuan et al found the mean ANC at cycle 1 to be 4.27 × 10 9 /L (95 % CI, 4.1-4.5 × 10 9 /L) [8]. This compares to 5.0 × 10 9/ L (95 % CI, 4.6-5.4 × 10 9 /L) for the current study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Chu-Yuan et al found the mean ANC at cycle 1 to be 4.27 × 10 9 /L (95 % CI, 4.1-4.5 × 10 9 /L) [8]. This compares to 5.0 × 10 9/ L (95 % CI, 4.6-5.4 × 10 9 /L) for the current study.…”
Section: Discussionsupporting
confidence: 56%
“…However, the completion rate in the current study was 82 %, which compares to 91 % [8] and 75 % [9] in other studies.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In other tumor types lymphopenia has correlated with lower disease-free survival, particularly with the use of chemotherapy [6870]. Reconstituting the immune system is thus an important goal of our BMT platform.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, mounting evidence suggests that the presence of the systemic inflammatory response, reflected in routine hematology, has a decidedly protumor capacity leading to poor prognosis in a host of malignant neoplasms 69. Albumin and globulin, the major constituents of serum proteins, have a vital effect on the systemic inflammatory response.…”
Section: Introductionmentioning
confidence: 99%